أثر العمالة المؤهلة على زيادة إنتاجية المؤسسة دراسة حالة المؤسسة الوطنية للدهن وحدة سوق اهراس - حليمة معيوف; إيمان رميكي (My University, 2021)
The need to pay attention to human resources is increasing due to the increased awareness of the owners of institutions of the importance of the human resource as a strategic asset of the institution's assets and a fundamental determinant of the effectiveness of the institution. performance, and in order to respond to rapid changes in the business environment, attention must be paid to it through many means, among which: The backbone of all the efforts made by these institutions towards development and improvement productivity, the latter having led to research into its determinants and methods of measurement, analysis of the factors that affect them and to provide solutions to help increase them and study their impact on costs and sales. This study aims to understand the reality of the employment of skilled labor by the National Oil Corporation - Souk Ahras branch - and its impact on its productivity. The study relied on the descriptive approach in the theoretical aspect, and the analytical approach in the practical aspect, where the questionnaire tool was used to know the opinions of the study sample. Comprised of 25 officials from the National Oil Corporation and Souk Ahras Unit, the results were analyzed on the statistical program spss, and the study results were tested using statistical methods. This study concluded that there is a positive effect between skilled labor and firm productivity. Finally, the study recommended the need to sensitize the institution to the need to continue paying attention to its human resources and individual skills through the development and rehabilitation of its workforce as much as possible due to of its ability to increase the productivity of the institution. .......................................................... تتزايد الحاجة إلى الاهتمام بالموارد البشرية نتيجة لزيادة وعي أصحاب المؤسسات بأهمية المورد البشري باعتباره أصلاً استراتيجياً من أصول المؤسسة ومحدداً أساسياً لفعالية المؤسسة. الأداء، ومن أجل الاستجابة للتغيرات السريعة في بيئة الأعمال، والاهتمام ويجب السداد لها من خلال وسائل عديدة، من بينها: العمود الفقري لجميع الجهود التي تبذلها هذه المؤسسات نحو التنمية وتحسين الإنتاجية، وقد أدى هذا الأخير إلى البحث في محدداتها وطرق قياسها وتحليل العوامل المؤثرة فيها و لتقديم حلول تساعد على زيادتها ودراسة تأثيرها على التكاليف والمبيعات. تهدف هذه الدراسة إلى التعرف على واقع توظيف العمالة الماهرة لدى المؤسسة الوطنية للنفط – فرع سوق أهراس – وأثره على إنتاجيتها. واعتمدت الدراسة على المنهج الوصفي في الجانب النظري، والمنهج التحليلي في الجانب العملي، حيث تم استخدام أداة الاستبيان لمعرفة آراء عينة الدراسة. وقد تم تحليل النتائج، المكونة من 25 مسؤولا من المؤسسة الوطنية للنفط ووحدة سوق أهراس، على البرنامج الإحصائي spss، كما تم اختبار نتائج الدراسة باستخدام الأساليب الإحصائية. وخلصت هذه الدراسة إلى وجود تأثير إيجابي بين العمالة الماهرة وإنتاجية الشركة. وأخيراً أوصت الدراسة بضرورة توعية المؤسسة بضرورة الاستمرار في الاهتمام بمواردها البشرية ومهاراتها الفردية من خلال تطوير وتأهيل القوى العاملة لديها قدر الإمكان لما لها من قدرة على زيادة إنتاجية المؤسسة.